ANALISIS HUKUM ISLAM DAN HUKUM PERDATA ATAS PUTUSAN PEMBATALAN PERKAWINAN: STUDI PUTUSAN NOMOR 2981/PDT.G/2024/PA.JS - Harvi Muhammad Fathiariq; Teguh Dwi Cahyadi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study analyzes the legal implications of the withdrawal of a marriage annulment lawsuit in Decision Number 2981/Pdt.G/2024/PA.JS, particularly concerning the legal status of a marriage conducted based on an alleged fictitious guardian (wali) and document forgery. Employing a normative juridical research method with a case study approach, the analysis is conducted from a multidisciplinary perspective, examining Islamic law, positive civil law, and criminal law. The findings reveal a fundamental discrepancy: under Islamic law, the marriage is considered void ab initio (fasakh), yet, following the lawsuit's withdrawal, under positive law, the marriage remains formally and administratively valid. This condition creates a procedural deadlock and long-term legal uncertainty susceptible to abuse of law. Furthermore, it does not nullify the separate criminal liability for document forgery under Article 263 of the Indonesian Criminal Code (KUHP).